Hambatan Dan Prospek Hukum Penyelenggaraan Jasa Notaris Secara Elektronik Di Indonesia Memasuki Era Society 5.0 - Chalid, Muhammad Ricky Ilham (UI Scholars Hub, 2022)
The development of technology, information and communication in the era of society 5.0 makes notaries have to be able to keep up with their ability to provide the best legal services, the best solution for notaries in facing the challenges of changing times is to implement cyber notaries and remote notaries, but this is not immune from the clash of the Indonesian legal system. Things that need to be considered are the reasons why Indonesia has not implemented it, such as the suitability of the application of long distance notaries and cyber notaries from common law to the Indonesian legal system, namely civil law and legal reasons that prevent them from being applied.